2022
DOI: 10.3389/fphar.2022.972900
|View full text |Cite
|
Sign up to set email alerts
|

The burden of carbapenem-resistant Enterobacterales infection in a large Thai tertiary care hospital

Abstract: Background: Carbapenem-resistant Enterobacterales (CRE) are resistant to several other classes of antimicrobials, reducing treatment options and increasing mortality. We studied the clinical characteristics and burden of hospitalized adult patients with CRE infections in a setting where treatment options are limited.Methods: A retrospective cohort study included adult inpatients between January 2015–December 2019 at Siriraj Hospital in Bangkok, Thailand. Clinical and microbiological data were reviewed.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(70 reference statements)
0
1
0
Order By: Relevance
“… 36 Patients with CRE infection have a complex etiology, long hospitalization, poor prognosis, and high mortality, posing great challenges for clinical treatment. 37 38 Moreover, the medical costs of patients with CRE were approximately three times higher than those of non-CRE patients, making CRE an economic burden worldwide.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Patients with CRE infection have a complex etiology, long hospitalization, poor prognosis, and high mortality, posing great challenges for clinical treatment. 37 38 Moreover, the medical costs of patients with CRE were approximately three times higher than those of non-CRE patients, making CRE an economic burden worldwide.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Tangsawad et al. reported a notably high in‐hospital mortality rate of 68.33%, 24 potentially attributed to differing outcome definitions. While previous studies have explored risk factors influencing mortality in CRE‐BSI patients, 3 , 4 , 5 none have specifically assessed the co‐occurrence of carbapenemase genes.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Our study revealed a 14-day mortality rate of 35.1% following the onset of CRE-BSI, consistent with rates observed in low-and middle-income countries, where the CRE-BSI mortality rate stood at 35%, with bla NDM-1 emerging as the predominant carbapenemase gene, followed by bla OXA-48 . 23 Tangsawad et al reported a notably high inhospital mortality rate of 68.33%, 24 potentially attributed to differing outcome definitions. While previous studies have explored risk factors influencing mortality in CRE-BSI patients, [3][4][5] none have specifically assessed the cooccurrence of carbapenemase genes.…”
Section: Discussionmentioning
confidence: 99%